PPV May Be a Starting Point to Achieve Circulatory Protective Mechanical Ventilation - Su, Longxiang; Pan, Pan; He, Huaiwu; Liu, Dawei; Long, Yun (Frontiers in Medicine, 2021)
Pulse pressure variation (PPV) is a mandatory index for hemodynamic monitoring during mechanical ventilation. The changes in pleural pressure (Ppl) and transpulmonary pressure (PL) caused by mechanical ventilation are the basis for PPV and lead to the effect of blood flow. If the state of hypovolemia exists, the effect of the increased Ppl during mechanical ventilation on the right ventricular preload will mainly affect the cardiac output, resulting in a positive PPV. However, PL is more influenced by the change in alveolar pressure, which produces an increase in right heart overload, also resulting in high PPV. In particular, if spontaneous breathing is strong, the transvascular pressure will be extremely high, which may lead to the promotion of alveolar flooding and increased RV flow. Asynchronous breathing and mediastinal swing may damage the pulmonary circulation and right heart function. Therefore, according to the principle of PPV, a high PPV can be incorporated into the whole respiratory treatment process to monitor mechanical ventilation cycle damage/protection regardless of controlled ventilation or spontaneous breathing. Through the monitoring of PPV, the circulation protection of mechanical ventilation can be guided at bedside in real time by PPV.